ELABORACIÓN DE UN PLAN DE MARKETING PARA LA COMPAÑÍA DE TAXIS ALAMOREÑA S.A EN EL CANTÓN PUYANGO - Maza Moncada, Estefanny Lucia (2015)
This thesis project aims to put into practice what I learned in the years of study of the career of Business Administration to develop a marketing plan to achieve greater business development, performing internal and external study to see the main problems afflict and see the reality of the company. Besides being essential for obtaining requisite degree of commercial engineer. The present research is aimed at customers of our service, seeking to improve its quality in order to meet the different needs of the population and thus help the business development and which contribute to the economic development of the Company Alamoreña taxis s.a Puyango Canton, improving quality its activities, knowing seize it in a proper way will provide us with higher incomes and achieving greater profit and improving the business development of the same. This study considered relevant and important conceptual elements that constitute the literature base for the development of this research. Within the methods and techniques used consists deductive, analytical, historical, comparative, statistical method, which served to prepare and develop the objectives of the project and applied the same techniques as the direct observation interview the manager, the surveys partners, employees and customers that facilitated obtain the information needed to clarify the current situation of the company. After meeting the current reality of the company's strengths and weaknesses as well as its opportunities and threats said and combine them strategic, same 6 goals that allowed begin developing strategic proposal Marketing Company defined. Among the strategic objectives identified four objectives: Objective No. 1: Make a proposal in which the directors of the taxi company "Alamoreña" make agreements with both public and private institutions to reach an agreement where the company used to provide tourist services to the general public with In order to generate greater competitiveness and company recognition. Objective 2: Consider the arrangement of units in good condition and comfortable in order to offset the price with the service provided. Objective 3: Improve waiting times staff provides users and designing an advertising program through radio spots in order to make known the services offered by the company. Objective 4: Improving infrastructure in order that it can provide an excellent image of the company. The marketing plan to be implemented amounts to a total of $ US $ 3,213. Implementation of this plan will allow the company to achieve greater development and positioning in the transport market. Finally, conclusions and recommendations has been determined, then the study and which will be exposed to the attention of the directors of the company for further implementation are presented.